A Segmental Fracture of Humerus with Ipsilateral Forearm Fracture: A Rare Variant of Pediatric Floating Elbow Injury - Joshi, Ruban Raj (Journal of Lumbini Medical College, 2017)
Introduction: Simultaneous segmental humerus fracture with ipsilateral forearm is an uncommon injury and scarcely mentioned in the literature. Case report: We present a case report on such a complex injury in a 9-year old child after falling down from the first floor of his house while playing. The injury pattern consists of ipsilateral supracondylar fracture humerus with distal humerus and ipsilateral distal forearm fracture. Open reduction and pinning of the both injuries was obtained. Conclusion: Ipsilateral multiple fractures in children often result from high energy trauma and are associated with complications. Immediate reduction and fixation is required. If satisfactory reduction cannot be achieved by closed technique, open reduction should be considered to avert additional soft tissue injury and forthcoming complications. J. Lumbini. Med. Coll. Vol 4, No 2, July-Dec 2016, page: 108-110 DOI: https://doi.org/10.22502/jlmc.v4i2.102